Deciphering Hussein Huzni Mukriani's Historiography: A Critical Examination of “The History of the Soran Princes” - Othman, Hardi Hama Saeed; Abdalla, Shabaz (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research delves into Hussein Huzni Mukriani's approach to historical writing, specifically examining his book titled